Spatial and Temporal Effects of Whale Watching on a Tourism-Naive Resident Population of Bottlenose Dolphins (Tursiops truncatus) in the Humboldt Penguin National Reserve, Chile - Toro, Frederick; Alarcón, Jaime; Toro-Barros, Bárbara; Mallea, Gabriela; Capella, Juan; Umaran-Young, Clara; Abarca, Paulette; Lakestani, Nelly; Peña, Claudia; Alvarado-Rybak, Mario; Cruz, Franco; Vilina, Yerko; et al. (Frontiers in Marine Science, 2021)
Standardized measures of behavior can be powerful tools for assessing the impact of whale watching activities on natural populations of cetaceans. To determine the possible impact of tourism on dolphins between a period without whale watching (1989–1992) (T1) and a period with whale watching (2010–2020) (T2), we examined the changes in the rate of surface behaviors, the group size of long-time resident bottlenose dolphins living in the waters of the Humboldt Current off Chile, and for T2 alone, we compared these differences between two localities, the Punta de Choros and Chañaral de Aceituno coves. We observed a significant decrease in the group size of the resident population and in the frequency of surface events associated with the absence and presence of tourism. For T2, we observed significant differences for the frequency of surface events between the Chañaral de Aceituno and Punta de Choros coves and differences in the frequency of surface events at different hours of the day. This was associated with the number of vessels at the time of the encounter. In addition, we observed for T2 that the most observed instantaneous response of the dolphins to the presence of tourist vessels was to avoid the boats, while approaching the boats was the least observed response. The number of vessels present in each dolphin encounter was the most important variable for our model as it explains these differences. These results show that tourism vessels have a significant impact on dolphin behavior and sociability, while the same population of dolphins have different spatial and temporal responses to different impacts of tourism. Further studies are needed to establish whether changes in the rate of surface behaviors are associated with higher levels of stress in dolphins and with effects on their health and reproductive success in the long term.